2014
DOI: 10.1182/blood-2013-10-530089
|View full text |Cite
|
Sign up to set email alerts
|

Novel FV mutation (W1920R, FVNara) associated with serious deep vein thrombosis and more potent APC resistance relative to FVLeiden

Abstract: Key Points FVNara (W1920R), associated with serious deep vein thrombosis, is more resistant to APC relative to FVLeiden (R506Q). This mechanism results from significant decreases in FVa susceptibility to APC and FV cofactor activity for APC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 43 publications
2
64
3
Order By: Relevance
“…To achieve comparable levels of FVa Nara inactivation, >50 nmol/L protein S was required. These results suggest that the reduced inactivation of FVa Nara observed in Figures C‐F is unlikely to be related to decreased phospholipid binding alone, but rather to a combination of decreased affinity of FVa Nara toward both the phospholipid membranes and protein S. Of note, Nogami and colleagues showed lack of cleavage of FVa Nara at Arg306, which is completely dependent upon phospholipids and enhancement by protein S …”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…To achieve comparable levels of FVa Nara inactivation, >50 nmol/L protein S was required. These results suggest that the reduced inactivation of FVa Nara observed in Figures C‐F is unlikely to be related to decreased phospholipid binding alone, but rather to a combination of decreased affinity of FVa Nara toward both the phospholipid membranes and protein S. Of note, Nogami and colleagues showed lack of cleavage of FVa Nara at Arg306, which is completely dependent upon phospholipids and enhancement by protein S …”
Section: Resultsmentioning
confidence: 84%
“…Nogami et al. recently identified the homozygous FV Nara mutation (FV W1920R) in a boy with recurrent DVT, whose phenotype was attributed to severe APC resistance of the mutant FV . The authors suggested that APC resistance may be caused by disruption of an APC interaction site.…”
Section: Discussionmentioning
confidence: 99%
“…Potential candidate mechanisms that do not involve the degradation of fVa or fVIIIa but are consistent with known functions of pS and fV include (1) the destabilization of the signaling-competent conformation of the TF complex secondary to physical interactions of B domain-containing fVa with fXa 49 and of pS with TF and fXa 50 , and/or (2) the recruitment of TF pathway inhibitor a (TFPIa) to the TF-fVIIa-fXa complex via interaction of pS with the TFPIa K3 domain or of the fV B domain with the carboxyterminal fragment of TFPIa (reviewed in Wood et al 51 ). It also remains to be clarified whether other naturally occurring fV variants such as fV Liverpool (I359T), 52 fV Nara (W1920R), 53 fV released from platelets, 54 or fV present in homozygous carriers of the fV R2 haplotype 11,[55][56][57] would exhibit similarly defective cofactor function for the inhibition of TF signaling by aPC as does fV Leiden.…”
Section: Discussionmentioning
confidence: 99%
“…1 Since the affected amino acid residue is located in the light chain of FV, far from the known APC-cleavage sites, this discovery may afford new insights into the molecular mechanisms of APC resistance.…”
Section: Elisabetta Castoldi 1 1 Maastricht Universitymentioning
confidence: 99%
“…The interesting study by Nogami et al describes a 13-year-old Japanese boy who developed recurrent venous thrombosis during oral anticoagulant treatment. 1 The patient had reduced FV levels (40 IU/dL antigen, 10 IU/dL activity) and pronounced APC resistance (see figure), prompting FV gene sequencing. This revealed a novel homozygous missense mutation (Trp1920→Arg, FV Nara ) in the C1 domain of FV, which was not found in 50 healthy Japanese people.…”
Section: Elisabetta Castoldi 1 1 Maastricht Universitymentioning
confidence: 99%